Metal complexes in cells: from design of catalytic antioxidants to imaging metal ions and designing metal-based probes in X-ray fluorescence and IR-imaging, a multidisciplinary collaborative journey in bioinorganic chemistry and inorganic chemical biology - Policar, Clotilde; Delsuc, Nicolas; Bertrand, Hélène Charlotte (Comptes Rendus. Chimie)
Bioinorganic chemistry and inorganic chemical biology are multidisciplinary fields dealing with metal ions in biological systems. In this article we will describe a research journey in these fields. This journey will take us from chemical design of inorganic metal complexes with a biological activity (catalytic antioxidants) or a biological interest (metal-based probes) and their characterization out of cellular context, typical of bioinorganic chemistry, to their studies in cells, typical of chemical biology.First, we will focus on the description of a bio-inspired strategy to design metal-based catalytic antioxidants. Starting from the description of the main features of an antioxidant cell-protecting metalloenzyme, the superoxide dismutase (SOD), we will delineate the main parameters to be controlled to design low-molecular weight (LMW) metal complexes meant to mimic its activity: choice of the metal cation, tuning of the redox potential, and modulation of the charge. The effect of the hydration level and inertness with regard to metal ion release have also been explored. Methods to quantify the SOD-like activity, out of cellular context and in cells, and analysis of the integrity of the metal-based antioxidant in cells (through ion mobility coupled with mass spectrometry) will be described. Strategies to develop peptide-based metal complexes through conjugation of a LMW complex with peptides aimed at targeting specific organelle will be presented. Peptides can also be used to coordinate the metal ion: a combinatorial approach, with an activity-based screening, or and a rationale design using three-stranded coil-coiled, will also be presented.The cellular activity of a molecule is strongly dependent on its sub-cellular location. A second focus of this article will be X-ray fluorescence imaging and infra-red microscopy, as techniques to image metal cations and metal-carbonyls in cells using the metallic core (M and M(CO)x). After a brief overview, we will describe how metal-based probes can be developed, as trackers of organelles or tags, with application to mitochondria tracking and to the imaging of the Mn-based SOD mimics previously described.Overall, we hope this this story will provide an insight of what are bioinorganic chemistry and inorganic chemical biology, showing how artificial metal-based systems can be chemically designed, associated with their direct study in cells.